La failia Notonectidae (Heteroptera) en Nicaragua - Mazzucconi, S.A.
(Es, En)
Ilus., 26 ref.
Keywords: NOTONECTIDAE; HETEROPTERA; INSECTA; ESPECIES NUEVAS; IDENTIFICACION; NICARAGUA; REVISTA NICARAGUENSE DE ENTOMOLOGIA